Optimal monetary policy in a hybrid New Keynesian model with a cost channel - Mikael Bask (Bank of Finland, 2007)
This study shows that an expectations-based optimal policy rule has desirable properties in a standard macroeconomic model incorporating a cost channel for monetary disturbances and inflation rate expectations that are partly backward-looking. Specifically, optimal monetary policy under commitment is associated with a determinate REE that is stable under learning, whereas, under discretion, the central bank has to be sufficiently inflation averse for the equilibrium to have these properties.
URN:NBN:fi:bof-20140807507
Keywords: E52; E61; 330; commitment; determinacy; discretion; expectations-based rule; least squares learning